Grammatical Error Patterns and Syntactic Processing Bottlenecks in L2 Arabic Oral Reading (Qirāʾah Jahriyyah) - Yazid Abdus Salam; Musta’in (Darul Yasin Al Sys, 2026)
Oral reading of unvowelized Arabic texts (qirāʾah jahriyyah / قراءة جهرية) requires the real-time integration of syntactic and morphological knowledge. Although previous research has documented general grammatical difficulties in second-language Arabic, the cognitive-processing mechanisms underlying breakdowns during live text vocalization remain underexplored. This qualitative case study employed Error Analysis to examine transcribed oral-reading performances on the diagnostic text Naṣāʾiḥ al-Ab wa Ijtihād al-Ibn among four focal participants in the Program Iman Specialization (Al-Program Al-Takhassusi) at STAI Ali Bin Abi Thalib Surabaya. The findings showed that grammatical errors clustered systematically around inflectional case assignment (iʿrāb / إعراب), construct-state formation (iḍāfah / إضافة), and complement realization (mafāʿīl / مفاعيل). The analysis further identified a Nominative Default Bias (Marfūʿāt Default / الانحياز الافتراضي للمرفوعات), whereby learners tended to produce nominative forms under cognitive overload, as well as a Declarative–Procedural Gap, in which their demonstrated mastery of grammatical rules in isolated ʿilm al-naḥw (علم النحو) exercises did not transfer to continuous oral reading. These findings indicate that oral-reading deviations arise primarily from real-time syntactic-processing bottlenecks rather than underlying grammatical-competence deficits. The study contributes to second-language Arabic acquisition research by distinguishing online processing failure from declarative grammatical knowledge and highlights the need to reorient Arabic instruction from static rule memorization toward speeded sentence-parsing exercises and targeted oral corrective feedback.